IGHV mutational status and outcome for patients with chronic lymphocytic leukemia upon treatment: a Danish nationwide population-based study - Rotbain, Emelie Curovic (Haematologica, 2020)
Patients with chronic lymphocytic leukemia and unmutated immunoglobulin heavy-chain variable region gene (IGHV) have inferior survival from time of treatment in clinical studies. We assessed real-world outcomes based on mutational status and treatment regimen in a nationwide population-based cohort, comprising all 4,135 patients from the Danish chronic lymphocytic leukemia registry diagnosed between 2008 and 2017. In total, 850 patients with known mutational status received treatment: 42% of patients received intensive chemoimmunotherapy consisting of fludarabine, cyclophosphamide plus rituximab, or bendamustine plus rituximab; 27% received chlorambucil in combination with anti-CD20 antibodies or as monotherapy, and 31% received other, less common treatments. No difference in overall survival from time of first treatment according to mutational status was observed, while treatment-free survival from start of first treatment was inferior for patients with unmutated IGHV. The median treatment-free survival was 2.5 years for patients treated with chlorambucil plus anti-CD20, and 1 year for those who received chlorambucil monotherapy. The 3-year treatment-free survival rates for patients treated with fludarabine, cyclophosphamide plus rituximab, and bendamustine plus rituximab were 90% and 91% for those with mutated IGHV, and 76% and 53% for those with unmutated IGHV, respectively, and the 3-year overall survival rates were similar for the two regimens (86-88%). Thus, it appears that, in the real-world setting, patients progressing after intensive chemoimmunotherapy as first-line therapy can be rescued by subsequent treatment, without jeopardizing their long overall survival. Intensive chemoimmunotherapy remains a legitimate option alongside targeted agents, and part of a personalized treatment landscape in chronic lymphocytic leukemia, while improved supportive care and treatment options are warranted for unfit patients.